Removing recalcitrance to the micropropagation of five farmer-preferred cassava varieties in Côte d’Ivoire by supplementing culture medium with kinetin or thidiazuron - Seka, John Steven S.; Kouassi, Modeste K.; Yéo, Edwige F.; Saki, Flavie M.; Otron, Daniel H.; Tiendrébéogo, Fidèle; Eni, Angela; Kouassi, Nazaire K.; Pita, Justin S. (Frontiers in Plant Science, 2025)
In vitro micropropagation is a rapid method of multiplying healthy planting material to control Cassava mosaic disease (CMD), one of a major constraint to cassava production in Africa. However, some cassava varieties have a low propagation ratio under in vitro conditions. The main objective of this study was to improve the in vitro propagation rate of five difficult to grow, farmer-preferred cassava varieties using plant growth regulators. Microcuttings from in vitro plantlets of five recalcitrant cassava varieties (Agbablé 3, Ampong, Bayérè, Bocou 5, Olékanga) were evaluated for their capacity to rapidly regenerate plantlets. Time to root or leaf formation, number of nodes, number of roots, and the in vitro plantlet length were evaluated on nine culture media combinations. We found that among all the cassava varieties studied, the shortest times for leaf (4 to 7 days) or root (9 to 14 days) formation were recorded when the two types of MS media were supplemented with kinetin and thidiazuron as well as on the medium contain half-strength MS without these plant growth regulators. These two hormones evaluated were better for regeneration of leaves, nodes and elongation of in vitro plantlets with optimum concentration of 5 and 10 nM or thidiazuron, and 0.12 or 0.24 µM for KIN. A survival rate between 85-91% was recorded under tunnel conditions and the plantlets appeared to be morphologically normal. The information obtained during this study will be useful for mass multiplication programs of elite cassava varieties.